Overseas complaints: preliminary notes on the problem of slavery through the perspective of Portuguese-Brazilian authorities and slave owners in the 18th century (Ágora Journal, 2024)
Attentive to the most recent developments in specialized historiography on the slavery of Africans and their descendants practiced in the Portuguese-Brazilian world of the eighteenth century, as well as in studies that have been renewing knowledge about the administration of justice in Portugal and its overseas domains, this article will draw on some cases that occurred in three of the captaincies with the largest contingents of slaves in the then State of Brazil, reported in the documentation stored in the Overseas Historical Archive in Lisbon, Portugal, to advance the understanding of how masters and state authorities dealt with the problem of slavery in the Portuguese-Brazilian world of the eighteenth century.
Keywords: slavery; portuguese administration; claims.